Development and Analysis of Microwave Cavity and Magnetic Shielding for Rubidium Atomic Clock - Raghuwanshi, Satyendra Singh (My University, 2009)
The fabrication design of microwave cavity and the magnetic field shielding factor are two import considerations in designing the physics package of the Rubidium atomic clock. The microwave cavity mode selection and machining of the cavity are based on the specific application. In this thesis we have discussed the development of microwave cavity in TE111 mode as the size is an important parameter. The cavity finish is another important aspect and software simulation plays central role in deciding the quality factor (Q) and uniformity of the field pattern. In atomic clock applications the tolerance limit are very small. In the work reported in this thesis these points have been addressed adequately. The magnetic shielding is also an important issue as the external magnetic field fluctuations can reduce the frequency stability. In the thesis various factors have been analyzed so that an optimum magnetic shielding factor may be realized.
M.E. ()
Keywords: Rubidium clock; Microave cavity, Magnetic sheilding